The Concept of Environmental Ethics in The Manuscript of La Galigo - Aaisyah, Sitti (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2018)
The main object of this research is the episode of Ritumpanna Walenrengnge (the cut down of Walenreng tree) from the manuscript of La Galigo. The mentioned manuscript then analyzed by using environmental ethics approach. This study aims to explain the concept of relations between humans and nature in the manuscript, and also to find environmental ethics view within the manuscript. This study was conducted through library research using descriptive, verstehen, hermeneutic, and heuristic methods. The study process started from preparing the research materials, followed by data gathering, research data systematization, results analysis and concluded with critical reflection. The manuscript of La Galigo contains cosmological explanation of Buginese people. Similar to other Eastern cultural features, the mythology of La Galigo also shows strong attachment between humans and nature. This feature is pictured by Sawerigadingâs ritual and persuasive effort to cut down Welenreng tree for noble and important cause. It is generally explained that, Ritumpanna Welenrengnge has an anthropocentrism pattern. In environmental ethics discourse, anthropocentrism is considered as the cause of every environment exploitation. This study draws different line from negative understanding of anthropocentrism, and focusing on important spiritually enlightened human aspect so that they are able to do positive fundamental changes for the sake of environment. Keywords: La Galigo, environmental ethics, anthroposentrism.